Intertextuality in Flavian Epic Poetry Contemporary Approaches - Coffee, Neil ca. 20./21.Jhd; Forstall, Christopher W. ca. 20./21. Jahrhundert; Galli Milić, Lavinia; Nelis, Damien ca. 20./21. Jh (Trends in Classics - Supplementary Volumes, 2020)
This collection of essays reaffirms the central importance of adopting an intertextual approach to the study of Flavian epic poetry and shows, despite all that has been achieved, just how much still remains to be done on the topic. Most of the contributions are written by scholars who have already made major contributions to the field, and taken together they offer a set of state of the art contributions on individual topics, a general survey of trends in recent scholarship, and a vision of at least some of the paths work is likely to follow in the years ahead. In addition, there is a particular focus on recent developments in digital search techniques and the influence they are likely to have on all future work in the study of the fundamentally intertextual nature of Latin poetry and on the writing of literary history more generally